Advanced Buffering Acidic Aqueous Electrolytes for Ultra‐Long Life Aqueous Zinc‐Ion Batteries. Issue 21 (22nd April 2022) - Zhao, Xuesong; Zhang, Xuan; Dong, Ning; Yan, Mengdie; Zhang, Fenglin; Mochizuki, Kenji; Pan, Huilin
Abstract: Mild aqueous Zn batteries have attracted increasing attention for energy storage due to the advantages of high safety and low cost; however, the rechargeability of Zn anodes is one major issue for practical applications. In this work, an effective approach is proposed to improve the reversibility and stability of Zn anodes using advanced acidic electrolytes. A trace amount of acetic acid (HAc) is employed as a buffering agent to provide a stable pH environment in aqueous Zn electrolytes, and thus suppress passivation from precipitation reactions on Zn electrodes. Meanwhile, tetramethylene sulfone (TMS) is introduced as the critical component to stabilize the Zn anodes in the acidic electrolyte. TMS greatly strengthens the hydrogen‐bonding network with reduced H2 O activity and extends the electrochemical window of acidic electrolytes. With the optimal 3 m Zn(OTF)2 in (H2 O‐HAc)/TMS acidic electrolyte (pH 1.6), the Zn electrode exhibits a coulombic efficiency of >99.8% and smooth Zn deposition. The Zn‐V2 O5 full cell demonstrates ultra‐stable cycling over 20 000 cycles with a low decay rate of 0.0009% for each cycle at a negative/postive capacity ratio of 6.5. This work provides an insightful perspective to stabilize Zn electrodes by regulating the pH environment and limiting the H2 O activity simultaneously for long‐life Zn anodes. Abstract : The rechargeability of Zn anodes is one major issue for practical applications of aqueous Zn batteries. An advanced acidic electrolyte with buffering agent acetic acid and functional tetramethylene sulfone can offer a stable pH environment and strengthened hydrogen‐bonding network, thereby enabling high stability of Zn anodes, wider voltage window, and ultra‐long cycle life for Zn‐V2 O5 full cells.